2020
DOI: 10.17085/apm.20076
|View full text |Cite
|
Sign up to set email alerts
|

Management of massive hemorrhage in pregnant women with placenta previa

Abstract: Patients with placenta previa are at risk for intra- and postpartum massive blood loss as well as increased risk of placenta accreta, a type of abnormal placental implantation. This condition can lead to serious obstetric complications, including maternal mortality and morbidity. The risk factors for previa include prior cesarean section, multiparity, advanced maternal age, prior placenta previa history, prior uterine surgery, and smoking. The prevalence of previa parturients has increased due to the rising ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 57 publications
0
9
0
2
Order By: Relevance
“…Generally, FFP transfusion is part of the massive transfusion protocol and should be considered if coagulopathy is suspected or con rmed by laboratory tests. The bene ts of transfusion of blood components and coagulation factors according to the massive transfusion protocol are the prevention of transfusion delay and coagulopathy correction [10].…”
Section: Discussionmentioning
confidence: 99%
“…Generally, FFP transfusion is part of the massive transfusion protocol and should be considered if coagulopathy is suspected or con rmed by laboratory tests. The bene ts of transfusion of blood components and coagulation factors according to the massive transfusion protocol are the prevention of transfusion delay and coagulopathy correction [10].…”
Section: Discussionmentioning
confidence: 99%
“…The results of an ultrasound examination conducted on March 1, 2021, showed that the mother had lateral placenta previa. Ultrasound examination is the main method recommended for detecting the location of abnormal placental implantation in the prenatal period, this examination is very important to make a proper diagnosis and determine the next management (Park and Cho, 2020). Speculum examination of digital vaginal examination is no longer recommended to diagnose placenta previa because it can cause massive bleeding (Merriam and D'Alton, 2017a).…”
Section: Discussionmentioning
confidence: 99%
“…Postpartum hemorrhage is frequently seen in maternal deaths and is a life-threatening phenomenon. In many studies, the anesthesiologist's approach, blood product transfusion, management, choice of ideal anesthetic manner, and postoperative care in life-threatening major bleeding cases have been examined [12,13]. In these studies, no superiority over the other has been stated, and inferences can be made at the recommendation level.…”
Section: Discussionmentioning
confidence: 99%